Proyects by direct management and custom proyects: solution or problem? Should we restrict them? - Morón Urbina, Juan Carlos (2016)
The author performs an analysis of the power that public entities have, under certain assumptions, to attend their own needs for goods, services and proyects without the need of contracting with private individuals, but using self-provision. The study covers the conditions under which entities can opt for this alternative, the limits that exist for it and the consequences they bring to the effectiveness of the entity’s management. In addition, the author proposes considerations that should be adopted by legislation in the field for greater control and verification of the conditions of effectiveness.